Eco-friendly silver nanoparticles from garlic: a novel therapeutic approach for treating Escherichia fergusonii wound infections - Abdelkhalig, Sozan M.; Ali, Arwa Gamal; Ghaly, Mohamed Farouk; Alharbi, Nada K.; Alharbi, Maha; Bendary, Mahmoud M.; Abousaty, Amira I. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionComplicated wound infections pose a significant challenge to patient recovery and healthcare systems, particularly due to the emergence of less common but highly resistant multidrug-resistant (MDR) pathogens that undermine the efficacy of conventional antibiotic therapies. This growing threat highlights the urgent need for innovative antimicrobial approaches. MethodologyIn this study, we synthesized eco-friendly silver nanoparticles (AgNPs) using garlic extract to combat complicated wound infections caused by atypical MDR pathogens. ResultsGenetic sequencing of 16S rRNA gene, aligned with phenotypic identification methods, confirmed that Escherichia fergusonii (E. fergusonii) as a significant atypical pathogen responsible for complicated wound infections, with a prevalence rate of 24% (12 out of 50 cases). Antimicrobial susceptibility testing revealed that all identified E. fergusonii strains exhibited MDR patterns. Garlic extract, analyzed using GC-MS and UPLC-ESI-MS/MS, identified sulfur-containing bioactive compounds such as allyl methyl trisulfide, dimethyl trisulfide, and allicin, which facilitated the biosynthesis of AgNPs. Stable, spherical AgNPs (15–20 nm) with strong antimicrobial properties were confirmed under optimal conditions (10 mL garlic extract, 40°C, pH 8.0). Their properties were validated using UV-Vis spectroscopy, XRD, and TEM. Antibacterial assays of AgNPs showed mean inhibition zones of 28±0.5 mm and MIC values of 100 µg/mL. TEM analysis revealed that AgNPs compromised bacterial membrane integrity, leading to structural damage, increased permeability, and leakage of intracellular contents. Simultaneously, they induced a concentration-dependent depletion of intracellular glutathione (GSH) in E. fergusonii, suggesting that both membrane disruption and oxidative stress synergistically contribute to bacterial cell lysis and death. A strong synergistic interaction was observed between AgNPs, used at a safe concentration below 50 µM as confirmed by cytotoxicity assays, and antibiotics such as ciprofloxacin, as evidenced by a fractional inhibitory concentration (FIC) index of 0.37. Time-kill assays demonstrated rapid bacterial eradication when AgNPs were combined with antibiotics such as ciprofloxacin. ConclusionThese findings underscore the promise of garlic-derived silver nanoparticles (AgNPs) as a fast-acting, eco-friendly option for treating complex wound infections caused by atypical multidrug-resistant (MDR) pathogens.